Paleo-sedimentary environment and lithofacies of Jurassic Da’anzhai Member in the Central Sichuan Basin-A case study of Well Ren’an 1 - Zhang, Rui; Zhang, Benjian; Wang, Minglei; Zhu, Haihua; Zhang, Shaomin; Tang, Wenqiang; Zhou, Hongfei; Li, Yucong; Bai, Rong; Jia, Min; Zhu, Yiqing; Han, Luyuan (Frontiers in Earth Science, 2023)
The Jurassic Da’anzhai Member in Sichuan Basin is an important target for shale oil exploration. Whole rock X-ray diffraction analysis, thin section, SEM and TOC testing, as well as major and trace element analysis are used to analyze the relationship of lithofacies and pore types with the sedimentary environment of the Da’anzhai Member in the Central Sichuan Basin. The results show the Da’anzhai Member in the Well Ren’an 1 (RA1) is divided into six types of lithofacies, based on a three-level division method of mineral composition-TOC-mineral structure— namely, massive mud-bearing shell limestone lithofacies (F), thick argillaceous shell limestone lithofacies (E), laminated clay silt shale lithofacies (D), thin shell calcareous shale lithofacies (C), laminated shell-bearing shale lithofacies (B), and thick clay shale lithofacies (A). The pore spaces include intergranular pores, intergranular dissolution pores, authigenic calcite intergranular pores, authigenic quartz intercrystalline pores, intergranular pores of clay minerals or pyrite nodules, as well as organic pores. The Da’anzhai Member was deposited in a semi-deep to shallow lake sedimentary environment, with relatively low salinity. This strata experienced moderate-to-strong chemical weathering as a result of the semi-arid, warm and humid paleoclimate environmental conditions that persisted during its deposition; low weathering and dry paleoclimate conditions occurred periodically. Paleoenvironment is an important influence on the lithofacies and pore types of the Da’anzhai Member. The persistence of arid climate conditions contributed to a decline in water depth, relatively high salinity, low organic productivity, and the deposition of carbonate rocks that characterize lithofacies E and F; mostly intercrystalline pores formed in these lithofacies in response to the prevailing arid climate conditions. Conversely, warm, and humid climate conditions increased the inflow of fresh water, terrigenous debris, and nutrients into the lacustrine basin that led to the deposition of fine-grained sedimentary rocks of lithofacies A, B, and C. These lithofacies are characterized by abundant nano pores, such as clay intercrystalline pores and organic pores.